The Cambridge Companion to Foucault - Gutting, Gary (Cambridge Cambridge University Press, 2003)
For Michel Foucault, philosophy was a way of questioning the allegedly necessary truths that underpin the practices and institutions of modern society. The essays in this volume provide a comprehensive overview of Foucault's major themes and texts, from his early work on madness through his history of sexuality. Special attention is also paid to thinkers and movements, from Kant through current feminist theory, that are particularly important for understanding his work and its impact. This revised edition contains five new essays and revisions of many others, and the extensive bibliography has been updated.
Keywords: Foucault, Michel -- 1926-1984; 20th Century (1901-2000); Philosophy; France